2008
DOI: 10.1177/0363546507312168
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment for Osteochondrosis of the Humeral Capitellum

Abstract: Osteochondrosis of the humeral capitellum can be successfully treated conservatively if treatment is begun in an early stage of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 29 publications
0
131
1
1
Order By: Relevance
“…In general, early-stage OCD or stable lesion on the joint can be managed non-operatively with good outcomes [5,11]. In contrast, advanced OCD or unstable lesions generally require surgical management [10,29]. A variety of surgical techniques for OCD have been reported in the literatures with satisfied outcomes, such as debridement, drilling, fragment removal, fragment fixation, and autologous osteochondral mosaicplasty [16,26,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In general, early-stage OCD or stable lesion on the joint can be managed non-operatively with good outcomes [5,11]. In contrast, advanced OCD or unstable lesions generally require surgical management [10,29]. A variety of surgical techniques for OCD have been reported in the literatures with satisfied outcomes, such as debridement, drilling, fragment removal, fragment fixation, and autologous osteochondral mosaicplasty [16,26,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…This involves immediate cessation of aggravating activities that load the radiocapitellar joint, i.e., throwing, gymnastics, weightlifting [6,7,19,40,41]. Some authors advocate the use of a hinged elbow brace for a period of 1-6 weeks in the initial resting period to allow intermittent range of motion exercises to prevent stiffness, while others recommend rest without immobilization [6,19].…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Those patients who did not improve with 6 months of conservative therapy went on to surgery [40]. Griewe et al reported that patients with not only abnormal T1 signals but also abnormal T2 signals on MRI without rim enhancement or obvious defect (both indicative of stable lesions) can initially be treated conservatively.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Sclerosis, fissuring, and fragmentation of the capitellum are also frequently observed. Matsuura et al 6) classified osteochondrosis of the humeral capitellum according to three stages. Stage I was characterized by translucency.…”
Section: )mentioning
confidence: 99%